Chanting of “Kidung Tanggulangin” to Overcome Social Problems in the People of Tanggulangin District, Sidoarjo Regency - Satrya, Al Rosyid Anggi; Almaida, Zwita; Ardi, Fasya Amalia (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Sidoarjo mud affected most areas of Tanggulangin District, Sidoarjo Regency, East Java Province. Social problems and the dynamics of people's lives change over time due to the catastrophic failure of technology. The Company has an important contribution in helping the community through social innovation-based programs and activities for the sustainability of people's lives. Social innovation is presented to help the community solve current problems, especially those that occur in Tanggulangin District. Problems in Tanggulangin sub-district, among others: floods, waste issues and poverty that can be solved by environmental management. PT Pertamina Gas Operation East Java Area took part in giving the role as a company that has an operating location in Tanggulangin District. The innovation was named Kidung Tanggulangin with the main goal, namely: the management movement to protect vulnerable communities with environmental management. This contribution requires the support of other stakeholders to complement the role. The Kidung Tanggulangin program is carried out in the corridor of community empowerment which is implemented in a sustainable manner.